179: Integrating Developmental Services with School-Based Health Care: Feasibility, Efficacy and Relevance in a Universal Healthcare System. Issue 6 (1st June 2014) - Yang, F; Sgro, M; Freeman, S
Abstract: BACKGROUND: The School-based health center (SBHC) is an emerging model for developmental healthcare delivery in Canada. Despite access to universal healthcare, barriers such as language, cultural differences and transportation affect access for children in underserved populations in Canada. The Model Schools Pediatric Health Initiative is the first SBHC program in Ontario, Canada established to alleviate barriers inner city children face to accessing developmental care. As part of the program, pediatricians attend interdisciplinary monthly school based (school support team, SST) meetings to help identify which students require developmental assessments and then offer them through the participating SHBC. OBJECTIVES: To provide an update on the Model Schools Pediatric Health Initiative SHBC program with respect to feasibility and efficacy. DESIGN/METHODS: A retrospective chart review of all clinic users from November 2010 to January 2012 was conducted and a prospective longitudinal cross-sectional analysis was implemented from February 2012 to June 2013. Among those referred for developmental concerns, time from identification at the SST meeting to first developmental assessment at the SBHC was calculated. The feasibility metrics included the number of children who enrolled at the SBHC. The efficacy metrics included the proportion of enrolled children who attended the SBHC, the proportion of new diagnoses established, as well as wait times. RESULTS: In total, 1042 children enrolled at the SBHC and 443 (43%of those that enrolled) attended the SBHC. There were a total of 282 new diagnoses established at the SBHC and among these 181 (64%) were in the developmental diagnostic category. From March 2012 to April 2013, 41 students were referred for developmental assessments from the School Support Team (SST). Thirty-three assessments were completed at the time of analysis and the mean wait time from presentation at the SST to developmental assessment was 102 days. CONCLUSIONS: The SBHC has proven to be feasible and efficacious. This model relies on an integrated approach whereby pediatricians and school board professionals meet monthly to discuss and triage at risk students needing developmental assessments. This process allows for better understanding of school related problems and provides assessments within the school setting thereby eliminating some barriers to healthcare access. Relative to the standard of care this process is fast and efficient and creates an optimal setting to increase access to specialized developmental services for inner city children facing barriers to accessing health-care in Canada.